Gastric epithelial cell kinetics in the progression from normal mucosa to gastric carcinoma. Issue 2 (February 1996) - Cahill, R J; Kilgallen, C; Beattie, S; Hamilton, H; O'Morain, C
Abstract : Increased epithelial cell proliferation is associated with an increased risk of adenocarcinoma and is associated with Helicobacter pylori infection. The aim of this study was to assess both gastric epithelial cell proliferation and the influence of H pylori infection on cell kinetics in the progression from normal mucosa to gastric carcinoma. One hundred and forty four subjects were assigned to study groups based on diagnosis and H pylori status: microscopically normal mucosa and H pylori negative (n = 28); chronic active gastritis and H pylori positive (n = 83); atrophic gastritis (n = 9); intestinal metaplasia (n = 19); gastric carcinoma (n = 12). Gastric antral epithelial cell proliferation was assessed using the in vitro bromodeoxyuridine immunohistochemical technique and expressed as the labelling index per cent (LI%). Subjects with chronic atrophic gastritis, intestinal metaplasia or gastric cancer have increased gastric epithelial cell proliferation compared with normal mucosa (LI% mean (SEM): 5.14 (0.6), 4.68 (0.3), 6.50 (0.5) v 3.08 (0.2), p < 0.001). This increase in gastric epithelial cell proliferation was not influenced by H pylori status. Gastritis associated with H pylori had an increased LI% compared with normal controls or subjects with H pylori negative gastritis (4.98 (0.2) v 3.08 (0.2), 3.83 (0.2), p < 0.01). H pylori infection although associated with an increased epithelial cell proliferation in subjects with chronic gastritis, does not influence the increased epithelial cell proliferation seen in subjects with precancerous lesions or gastric carcinoma. This is further evidence that H pylori may be an initiating step in gastric carcinogenesis.